Research on Mechanical Properties of Cement Emulsified Asphalt Mortar Under the Influence of Water-to-Cement Ratios and Water-Reducing Agent - Ce Zhao; Huacheng Jiao; Bing Zhou; Fei Liu; Feilin Zhang; Yong Luo; Jie Yuan (Buildings)
To understand the mechanical behavior of CRTS (China Railway Track System) II cement emulsified asphalt mortar (CA mortar), this study tested the compressive strength and flexural strength of CA mortar at different ages under varying water-to-cement ratios and dosages of water-reducing agent. Based on X-ray diffraction (XRD) and scanning electron microscopy (SEM) results, the hydration products and microstructure of CA mortar at different ages were analyzed. The main conclusions are as follows. As the water-to-cement ratio increases, the compressive strength and flexural strength of CA mortar generally exhibit a decreasing trend. The strength increases rapidly in the early stages, with the 7-day compressive strength reaching over 80% of the 28-day compressive strength, and the 7-day flexural strength reaching over 93% of the 28-day flexural strength. As the dosage of water-reducing agent increases, both the compressive strength and flexural strength of CA mortar first increase and then decrease, with a reasonable range of water-reducing agent dosage being between 0.2% and 1.0%, and 0.5% is most appropriate. The hydration reaction of CA mortar is nearly complete at 3 days, with the increase in ages, the cement hydration slows down due to the coating action of asphalt, and the strength no longer changes greatly. Hydration products are mainly Ettringite, which is the main source of strength of CA mortar. After the emulsified asphalt breaks, it adsorbs onto the hydration products and sand surfaces, gradually forming a continuous phase, which enhances the structural toughness of the CA mortar.